SOX2 Promotes Cell Proliferation and Metastasis in Triple Negative Breast Cancer - Liu, Peng; Tang, Hailin; Song, Cailu; Wang, Jin; Chen, Bo; Huang, Xiaojia; Pei, Xiaoqing; Liu, Longzhong (Frontiers in Pharmacology, 2018)
This study explored the expression, biological function and prognostic role of SOX2 in triple negative breast cancer (TNBC). Quantitative real-time PCR (qRT-PCR) and immunohistochemistry (IHC) were used to detect the expression of SOX2 in TNBC cell lines and clinical tissues. MTT assay, Transwell assay, flow cytometry and xenograft mouse model were used to assess the biological functions of SOX2. It was found that SOX2 was up-regulated in both TNBC cell lines and clinical tissues. High expression of SOX2 was associated with shorter overall survival (OS) and disease free survival (DFS). Moreover, inhibition of SOX2 suppressed cell proliferation and invasion, induced cell apoptosis in vitro, and suppressed tumorigenesis and metastasis in vivo. In addition, analysis of TNM stage and lymph nodes infiltration among the 237 TNBC patients by paired χ2 test showed that SOX2 was inversely correlated with tumour status, our findings provided evidence that SOX2 acts as a tumour promoter in TNBC and inhibition of SOX2 could be a potential therapeutic strategy for TNBC.